2013
DOI: 10.1186/1743-8977-10-63
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle alterations induced by urban PM2.5 in bronchial epithelial cells: characterization of the process and possible mechanisms involved

Abstract: BackgroundThis study explores and characterizes cell cycle alterations induced by urban PM2.5 in the human epithelial cell line BEAS-2B, and elucidates possible mechanisms involved.MethodsThe cells were exposed to a low dose (7.5 μg/cm2) of Milan winter PM2.5 for different time points, and the cell cycle progression was analyzed by fluorescent microscopy and flow cytometry. Activation of proteins involved in cell cycle control was investigated by Western blotting and DNA damage by 32P-postlabelling, immunostai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(101 citation statements)
references
References 79 publications
8
93
0
Order By: Relevance
“…Oxidative DNA damage in lung cells has been extensively reported in in vitro and in vivo systems exposed to PM or UFPs (Gualtieri et al, 2012;Longhin et al, 2013;Meng and Zhang, 2007;Oh et al, 2011). Pb, a prevalent toxic metal component in ambient PM, is known to induce oxidative stress and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative DNA damage in lung cells has been extensively reported in in vitro and in vivo systems exposed to PM or UFPs (Gualtieri et al, 2012;Longhin et al, 2013;Meng and Zhang, 2007;Oh et al, 2011). Pb, a prevalent toxic metal component in ambient PM, is known to induce oxidative stress and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…A cytotoxic response was observed for organic nanoparticles generated by laboratory flame and by diesel engines (Manzo et al, 2010;Sgro et al, 2009). Longhin et al (2013) reported the correlation of OC and DNA damage in an urban environment. OC correlated with oxidative potential in the Long Beach harbour area and in traffic-exhaust-dominated areas (Gualtieri et al, 2011;Verma et al, 2011).…”
Section: Particulate Matter and Healthmentioning
confidence: 99%
“…Longhin et al examined the role of PM 2.5 organic fraction versus washed PM on the cell cycle alterations, and the results have shown that the metabolic activation of PM 2.5 organic chemicals cause damages to DNA and the spindle apparatus, and G2/M arrest and augmented ROS formation follow it, while washed PM had no such effects [30]. …”
Section: Resultsmentioning
confidence: 99%